Food associated pathogens [ - Danielsson-Tham, Marie-Louise , 1947-; Tham, Wilhelm (CRC Press, 2014)
"Food borne diseases associated with microbial pathogens are an important cause of human illness. Changes in both lifestyle and eating habits increase the opportunity for the transmission of pathogenic microorganisms in foods, for example, the consumption of raw foods implies risks for food borne infections and intoxications, as does the greater demand for refrigerated ready-to-eat foods, as some food borne pathogens are capable of growth even at refrigeration temperatures. The extended shelf life of many food items can threaten consumer's health. In addition, personal hygiene has worsened, and food workers? improper hand cleaning is increasingly implicated in food borne illness. The teaching of food safety needs to be reintroduced, even in primary education. The number of people susceptible to food borne disease has increased, especially among the population over 65 years of age. Thus, food microbiologists working with food-associated pathogens need to be familiar with the type of microorganisms associated with a food product in its natural state to be able to predict the general types of microorganisms expected in a particular food product. The food microbiologist must also be familiar with the incubation periods and clinical symptoms of different food borne diseases. The effective prevention of food borne diseases requires cooperation and open-mindedness among different authorities and professionals, e.g., physicians, medical officers, veterinarians, public health offi cers, food producers, national surveillance institutes, scientists, and government ministers and departments. Future food safety should be an important factor in trade, and countries with the best food safety will gain new international markets"